Perceived Service Quality in the Era of Sustainable Higher Education: Evidence from Teacher Training Institutions in Indonesia - Raharjo, Teguh Hardi; Oktarina, Nina; Permana, Dian Fithra (Asian Journal of Interdisciplinary Research, 2026)
Despite the growing popularity of sustainability practices in higher education institutions (HEIs), the specific factors influencing Perceived Service Quality (PSQ) in this context remain unclear. This study addresses this gap by examining the Sustainable Higher Education Service Quality (SHE-SQ) framework to identify drivers of PSQ. This investigation focused on Teacher Education Institutions (LPTK) in Indonesia. The research design used a quantitative cross-sectional approach. Data were collected through convenience sampling, yielding a sample of 320 respondents. Data analysis used Partial Least Squares Structural Equation Modeling with 5000 subsample bootstrapping runs to assess path outcomes. The results revealed a significant shift in student expectations. Job Quality and Student Skills Development had a positive and significant impact on PSQ. Meanwhile, Lecturer Profile, Curriculum, Infrastructure and Facilities, Management and Support Staff, and Safety and Security did not have a significant impact. The unexpected results of this study directly challenge the traditional paradigm of educational service quality. This study recommends that LPTK managers align their institutions' strategic focus on fostering graduate innovation in a dynamic labor market through industry collaborations, integrated internships, and competency certification. The study, the first to combine General Systems Theory with UI GreenMetric parameters, revealed that LPTK students place greater value on HEIs' services that foster personal growth through experiences and future career readiness.